The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.9734/ajbgmb/2020/v3i230084
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Antimicrobial Resistance of Enterobacteria Responsible for Urinary Tract Infections in Benin: Another Way to Control Antimicrobial Resistance

Abstract: Background: Infectious diseases are serious public health issue both in developing countries and industrialized nations. In developing countries, they are the main cause of high mortality rates. In the second group, existing resistance strains to antibiotics is developing and growing at an alarming rate. The purpose of this study was to produce data of national interest to implement sustainable control program against the spread of antimicrobial resistance strains in Benin. Methods: One hundred and ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…Similar finding were revealed in Cameroon by some authors Marbou and Kuete [15]; Ngalani et al [17] in the West region of the country. This result corroborates several studies conducted by researchers from other countries who worked on enterobacteria responsible for Urinary Tract Infections in Benin [5]. However, percentage obtained with almost all the bacterial species were lower than those obtained by Marbou and Kuete [15]; Ngalani et al [17].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar finding were revealed in Cameroon by some authors Marbou and Kuete [15]; Ngalani et al [17] in the West region of the country. This result corroborates several studies conducted by researchers from other countries who worked on enterobacteria responsible for Urinary Tract Infections in Benin [5]. However, percentage obtained with almost all the bacterial species were lower than those obtained by Marbou and Kuete [15]; Ngalani et al [17].…”
Section: Discussionsupporting
confidence: 90%
“…Imipenem and Amikacin therefore had good activity on enterobacterial strains. This trend has also been found by Ebongue et al [13]; Ngalani et al [17] in Cameroon and Dougnon et al [5] in Benin. In contrast, Hashemi et al [32] found higher resistance rates of around 19% to Imipenem and 30% to Amikacinin.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Urinary tract infection is the most common infectious disease in Africa. Victorien et al (2020) reported that urinary tract infections are the most common in general medicine and that the bacteria involved are mostly multiresistant. Indeed, the emergence and increasing spread of antimicrobial resistance is a real public health problem limiting the range of antibiotic molecules to be used.…”
Section: Discussionmentioning
confidence: 99%